Paradigma Pendidikan Holistik dalam Islam: Harmonisasi Aspek Kognitif, Afektif-Spiritual, dan Psikomotorik - Hoirun Nahdiyah; Maknunah; Mashun (STAI AL-AMIN, 2024)
Contemporary Islamic education faces the challenge of dichotomy between intellectual and spiritual development of learners, resulting in fragmented learning that impacts graduate quality. This conceptual article aims to construct a holistic education paradigm from Islamic perspective through harmonization of three fundamental dimensions: cognitive (aqliyah), affective-spiritual (ruhiyah), and psychomotor (jismiyah). Through philosophical-theoretical analysis of tarbiyah syumuliyyah (comprehensive education) concept, this study explores the epistemological foundation of holistic education in classical and contemporary Islamic thought. This study employs conceptual analysis method with hermeneutic approach to primary texts (Qur’an, Hadith) and secondary sources (classical scholars’ works and contemporary Muslim intellectuals). The analysis reveals that Islamic holistic education paradigm is based on the concept of insan kamil (perfect human) which integrates the development of intellect (‘aql) for critical thinking, heart (qalb) for spiritual piety, and body (jism) for practical skills. The integration of these three dimensions forms a dynamic balance reflecting the principle of wasathiyyah (moderation) in education. Recent research confirms the urgency of integrating these three domains in creating meaningful learning and producing graduates who are intellectually competent, spiritually mature, and practically skilled. Theoretical implications of this paradigm include reconstruction of non-dichotomous Islamic education curriculum, development of learning methods that activate all human potentials, and formulation of educational objectives oriented toward forming khalifah fil ardh. This article provides conceptual contribution to the development of Islamic education theory that is responsive to contemporary needs without losing the essence of spiritual values.